2009
DOI: 10.1051/0004-6361/200912592
|View full text |Cite
|
Sign up to set email alerts
|

Parkes H I observations of galaxies behind the southern Milky Way

Abstract: As part of our programme to map the large-scale distribution of galaxies behind the southern Milky Way, we observed 314 opticallyselected, partially-obscured galaxies in the Zone of Avoidance (ZOA) in the Crux and Great Attractor (GA) regions. An additional 29 galaxies were observed in the Vela ZOA survey region (because of the small numbers they are not discussed any further). The observations were conducted with the Parkes 64 m (210 ft) radio telescope, in a single-pixel pointed mode, reaching an rms noise l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 57 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…J1222-57. -Schröder et al (2009) have detected this galaxy in the OFF beam and associated it with WKK 0969 (which lies d 10.2 sep = ¢ to the southeast of our detection) as the only known galaxy in the area, while at d 6.2 sep = ¢ we find a galaxy that is not listed in the literature as the more likely counterpart.…”
Section: Appendix Notes To Individual Detectionsmentioning
confidence: 51%
See 3 more Smart Citations
“…J1222-57. -Schröder et al (2009) have detected this galaxy in the OFF beam and associated it with WKK 0969 (which lies d 10.2 sep = ¢ to the southeast of our detection) as the only known galaxy in the area, while at d 6.2 sep = ¢ we find a galaxy that is not listed in the literature as the more likely counterpart.…”
Section: Appendix Notes To Individual Detectionsmentioning
confidence: 51%
“…ii. We have cross-checked our detections with the nondetections in the deeper (but pointed) Parkes survey of optically selected galaxies in the southern ZOA by Kraan-Korteweg et al (2002) and Schröder et al (2009) and found no false positives (with the caveat that a pointed survey has a different selection function than a blind survey).…”
Section: Reliabilitymentioning
confidence: 91%
See 2 more Smart Citations
“…One of us (R.K.K.) contributed previously-unpublished measurements for 39 objects and we found redshifts in NED (NASA/IPAC Extragalactic Database) for five galaxies (Crook et al 2007;Guzzo et al 2009;Schröder et al 2009), leaving 997 objects to be observed.…”
Section: Observationsmentioning
confidence: 98%